A rare and challenging case of anaesthetic management of paediatric laryngo-tracheo-broncho-malacia for supraglottoplasty - Lalwani, Parin; Gupta, Babita (International Journal of Research in Medical Sciences, 2023)
Paediatric laryngotracheobronchomalacia is a rare and extremely challenging scenario with risk of complete airway collapse under general anaesthesia. Laryngomalacia causes collapse of the supralaryngeal structures during inspiration as it is associated with short aryepiglottic folds, redundant arytenoid mucosa prolapsing into the glottis and a long curled epiglottis. Tracheomalacia and tracheo-bronchomalacia are characterized by abnormally compliant trachea and major bronchi. Most of the general anaesthetic agents decreases the airway tone and may predispose these patients to unremmitable airway obstruction under anaesthesia. We report successful anaesthetic management of one-year-old child with laryngotracheobronhcomalacia posted for supraglotoplasty. This needs a profound understanding of the pathophysiology of the complex airway condition and the effects of various anaesthetic agents on airway.